(untitled) (Czech Journal of International Relations, 2002)
Steve Reicher – Nick Hopkins: Self and Nation. Categorization, Constestation and Mobilization. 1st ed. London: SAGE Publications, Thousand Oaks, New Delhi, 2001,XIII/242 stran, ISBN 0-7619-6919-5.